Variation of the seed and foliar phenolic contents of five wild forms of common bean (Phaseolus vulgaris L.) - Shaila Nayeli Pérez-Salinas; Rene Torres Ricario; Nancy Nohemí Rodarte Rodríguez; Heberto Iván Salas Ayala; Liliana Wallander Compeán (Tecnociencia Chihuahua)
The objective of the present study was to evaluate the seed and foliar phenolic composition from populations of wild Phaseolus vulgaris of Durango, Mexico. Seeds and leaves extracts were analyzed by HPLC-DAD, and UV-visible spectrophotometry. Analysis of variance were used to determine the capacity of the phenolic contents to discriminate between samples, the data were submitted to principal component analysis (PCA) and cluster analysis. The population with the highest content of phenolic compounds in both seed and leaves was the wild population of Nuevo Ideal and those that accumulated the lowest content of these compounds were Nombre de Dios and Canatlán. A total of 37 phenolic compounds in both seed and leaves from wild common bean were identified by HPLC–DAD. Wild species are important for the conservation of biodiversity, and for the genetic improvement of new varieties. Likewise, they could be used as forage, food or medicine, due to the high content of phytochemicals in seeds and leaf tissue, therefore, the information generated is relevant to knowledge about the characterization and diversity of wild Phaseolus species.